2014
DOI: 10.2147/dddt.s72394
|View full text |Cite
|
Sign up to set email alerts
|

CCL19 and CCL21 modulate the inflammatory milieu in atherosclerotic lesions

Abstract: Despite advances in the pharmacologic and interventional treatment of coronary artery disease, atherosclerosis remains the leading cause of death worldwide. Atherosclerosis is a chronic inflammatory disease, and elevated expression of CCL19 and CCL21 has been observed in ruptured lesions of coronary arteries of patients with myocardial infarction and carotid plaques of patients with ischemic symptoms, as well as in plasma of coronary artery disease patients. However, the exact role of CCL19 and CCL21 in athero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 47 publications
0
19
0
1
Order By: Relevance
“…As can be seen from the present proteomic studies, a large proportion of the changes in plasma levels of proteins in SPS or reduced GFR concerns proteins with signaling functions. A survey of the literature suggests that of the 30 changes specific for SPS, 18 promote, or are associated with, atherosclerosis38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59 (Table 2). The same is true for 12 of the 31 changes occurring in patients with both SPS and reduced GFR60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71 and for 10 of the 27 changes specific for reduced mGFR72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84 (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…As can be seen from the present proteomic studies, a large proportion of the changes in plasma levels of proteins in SPS or reduced GFR concerns proteins with signaling functions. A survey of the literature suggests that of the 30 changes specific for SPS, 18 promote, or are associated with, atherosclerosis38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59 (Table 2). The same is true for 12 of the 31 changes occurring in patients with both SPS and reduced GFR60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71 and for 10 of the 27 changes specific for reduced mGFR72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84 (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Until now, there is no information about a small molecule or another modulator that is directly targeted at CCL17. However, research results of virtual ligand screening research about small-molecule inhibitors of the CCL17–CCL4 interaction suggest that validation of CCL17 as a target to inhibit atherogenesis is feasible [160, 161].…”
Section: Drug Discovery and Potential Targets Based On The Inflammatimentioning
confidence: 99%
“…In humans, the increased level of CCL19 and CCL21 is correlated with atherosclerotic carotid plaques [161]. The modulation of CCL19 and CCL21 chemokines in LDLr –/– mice model reduced the level of pro-inflammatory cytokines, such as IL-12 and IFN-γ, which resulted in atherosclerotic plaque stabilization [161, 163].…”
Section: Drug Discovery and Potential Targets Based On The Inflammatimentioning
confidence: 99%
“…A previous study has shown a possible link between CCL19 and plaque destabilisation through recruitment of T cells and macrophages. 39 In a recent atherogenic mouse model study, 40 it was found that CCL19 had a significant role in cellular activation, especially of macrophages in atherosclerotic lesions. It was also noted that CCL19 influences the activation of leukocytes, lipid uptake of macrophages, and foam cell formation within atherosclerotic plaques.…”
Section: Discussionmentioning
confidence: 99%